Prevalência de enteroparasitoses em comunidades da periferia de Belo Horizonte: prevalência nos laboratórios das comunidades vs comunidades - Frederico Ferreira Gil (2012)
Parasitic diseases affect the quality of life for people around the world, being the intestinal characters the most prevalent, closely associated to poor hygiene, lack of sanitation and behavioral factors. In this work, using the structure of the Project SOL, we know the prevalence of intestinal parasites in clinical laboratories (LDAC-PBH) that serve four underserved communities on the outskirts of Belo Horizonte (Conjunto Santa Maria (CSM), Conjunto Jardim Felicidade (CJF), Alto Vera Cruz (AVC) and Vista Alegre (VA)), evaluating the association of this prevalence with the prevalence in the community, and also the association of prevalence in IPs with the prevalence in their families. Two questionnaires, Clinical and Health-Food were applied. The results were presented by the sum of the data. In LDAC-PBH, with a prevalence of 19%, 531 results of stool analysis were elected, 107 positive known Positive Indicators of parasitosis (PI+) and 424 negative, called Negative Indicators of parasitosis (PI-). In home visits, all PIs and family of PIs (FPI) were invited to participate in the study. In LAPI-UFMG, 981 samples were analyzed (PIs and FPIs), with a prevalence of 46.6% (Blastocystis - 30.1%, Endolimaxd nana - 14.3%, E. coli - 13.8%), with differences by age group. The prevalence was higher in FPI+, but without statistical significance, and there isn´t therefore, an association between the individual test be positive in the LDAC-PBH and their families are also positive (PI+ 50.6% vs 45.9% PI- - p= 0.302). There weren´t differences in symptoms reported by both groups of relatives, except as nausea / vomiting post prandial (p= 0.042), weight loss (p= 0.031) and asthenia (p= 0.012), which were the associated signs to the FPIs presenting at least 1 parasite. Filtration of water (44.7% vs 52.5% - p= 0.031) and washing of the food (49.2% vs 472.7% - p = 0.055) before consumption, can be effective to alleviate enteroparasites infection. The IP+ no impact on the determination of the prevalence in the communities studied; so, can´t be used as a marker of infection. The overall prevalence of intestinal parasites was very high, although almost all of the homes are supplied with treated water, suggesting that behavioral and educational factors may be related to increased infection by intestinal parasites in these communities.